2013
DOI: 10.1144/sp383.9
|View full text |Cite
|
Sign up to set email alerts
|

Antarctica and supercontinent evolution: historical perspectives, recent advances and unresolved issues

Abstract: The Antarctic rock record spans some 3.5 billion years of history, and has made important contributions to our understanding of how Earth's continents assemble and disperse through time. Correlations between Antarctica and other southern continents were critical to the concept of Gondwana, the Palaeozoic supercontinent used to support early arguments for continental drift, while evidence for Proterozoic connections between Antarctica and North America led to the 'SWEAT' configuration (linking SW USA to East An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
77
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 99 publications
(79 citation statements)
references
References 268 publications
(354 reference statements)
2
77
0
Order By: Relevance
“…Given its present position the evolution of the Rauer Terrane is critical to understanding the amalgamation of East Antarctica, and particularly the relative importance of 1000 and 530-510 Ma tectonothermal events in weld-ing together the various Archaean and Proterozoic crustal blocks (Zhao et al, 1995;Hensen and Zhou, 1995;Carson et al, 1996;Hensen and Zhou, 1997;Fitzsimons, 2000;Harley, 2003;Carson et al, 2007;Wang et al, 2007;Kelsey et al, 2007Kelsey et al, , 2008Boger, 2011;Harley et al, 2013). The Mather Paragneiss detrital zircon age spectra (upper intercepts of 2800-2400 Ma) and the protolith zircon age of the host tonalitic orthogniess (3268 ± 4 Ma) obtained in this study are consistent with the previously reported zircon dates from Archaean orthogneisses of the Rauer Islands, and confirm that the host orthogneiss surrounding the UHT paragneisses are Archaean in protolith age.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given its present position the evolution of the Rauer Terrane is critical to understanding the amalgamation of East Antarctica, and particularly the relative importance of 1000 and 530-510 Ma tectonothermal events in weld-ing together the various Archaean and Proterozoic crustal blocks (Zhao et al, 1995;Hensen and Zhou, 1995;Carson et al, 1996;Hensen and Zhou, 1997;Fitzsimons, 2000;Harley, 2003;Carson et al, 2007;Wang et al, 2007;Kelsey et al, 2007Kelsey et al, , 2008Boger, 2011;Harley et al, 2013). The Mather Paragneiss detrital zircon age spectra (upper intercepts of 2800-2400 Ma) and the protolith zircon age of the host tonalitic orthogniess (3268 ± 4 Ma) obtained in this study are consistent with the previously reported zircon dates from Archaean orthogneisses of the Rauer Islands, and confirm that the host orthogneiss surrounding the UHT paragneisses are Archaean in protolith age.…”
Section: Discussionmentioning
confidence: 99%
“…Timing of UHT metamorphism and tectonic implications Placing a strong time constraint on the UHT event in the Mather Paragneiss is critical for models of the development of the Rauer Islands, the Prydz Belt and the amalgamation of East Antarctica (Harley et al, 2013). The first indication that these paragneisses might record an event distinct in age from the Prydz Tectonic Event was reported by Zhou (1995, 1997), who obtained a 600 Ma Sm-Nd garnet-whole rock isochron for Mather Paragneiss SH/88/218.…”
Section: Relationships Between Archaean and Proterozoic Crustal Domaimentioning
confidence: 99%
See 1 more Smart Citation
“…Equivalent units in Madagascar are the Antongil Domain, with 3.3-3.1 Ga tonalite intruded by 2.6-2.5 Ga granite (Tucker et al,Figure 3. Cratons (>0.9 Ga) and Pan-African orogens (0.7-0.5 Ga) of Gondwana (modified from Gray et al, 2008;Meert and Lieberman, 2008;Harley et al, 2013 1999; Schofield et al, 2010), and the Masora Domain with similar protoliths but a stronger Pan-African overprint discussed further below (Tucker et al, 2011a;Key et al, 2011;Ichiki et al, 2015). Although Indian and African sides of the orogen both record 2.6-2.5 Ga magmatism, they are set apart by major magmatic events at 3.5-3.0 Ga in the former, and at 2.1-1.8 Ga and~1.0 Ga in the latter.…”
Section: Cratonic Margins Of the East African Orogenmentioning
confidence: 99%
“…It has been considered sourced from East Antarctica from rocks now buried under the ice sheet Saeed, 2008, 2011). Extensive Pan African belts are considered to underlie icecovered East Antarctica, based on rock systems exposed at the continental periphery, and is consistent with a Pacific-Gondwana population in zircon eroded from the Antarctic interior and deposited at the continental margins (Harley et al, 2013). Alternatively a much more distant source has been suggested involving the collision belt of East and West Gondwana along the East African Orogen (Squire et al, 2006;Maidment et al, 2013).…”
Section: Detrital Zircon Ages Have Shown That the Metasedimentary Sucmentioning
confidence: 83%